SMS reminders to improve outpatient attendance for public dental services: A retrospective study. (30th November 2021) - Stormon, Nicole; Sexton, Christopher; Chen, Cecilia; Hsu, Elizabeth; Chen, Pei‐Chen; McGowan, Kelly
Abstract: Patients who miss scheduled appointments reduce clinical productivity and delay access to care for other patients. Reminders have improved attendance for healthcare appointments previously, but it is not known if short message service (SMS) implementation reduces incidence of patients unable to attend (UTA) or who fail to attend (FTA) appointments in the public dental service. This paper studied the effectiveness of SMS reminders in increasing appointment attendance at outpatient public dental services in Queensland. Data were sourced from the adult service and the children and adolescent oral health service (CAOHS) at West Moreton Hospital and Health Service, a public dental service in Queensland. A total of 63, 238 appointments pre‐implementation of SMS reminders and 55, 028 appointments post‐implementation over a period of 2 years were analysed for rates of attendance, UTA and FTA. Characteristics of UTA and FTA appointments were analysed to identify factors that hindered improvement after implementation of reminders. For the CAOHS, the attendance rate decreased 4% (95% CI: 2%, 6%) following SMS implementation. The UTA rate also increased by 20% (95% CI: 15%, 25%). Following SMS implementation in the adult service, the attendance rate increased from 73.5 (95% CI: 72.6, 74.4) to 77.7 (95% CI: 76.6–78.8) per 100 appointments. The FTA rate post‐implementation was 1.08 (95% CI: 1.00, 1.16) times that from pre‐intervention, and the UTA rate decreased from 21.7 (95% CI: 21.2, 22.2) to 17.1 (95% CI: 16.6, 17.7) per 100 appointments. The SMS reminders had a mixed effect on the attendance, UTA and FTA rates for the CAOHS and adult services. Reminders reduced the rates of UTA for the CAOHS service and increased the rate of attendance for the adult service. There was an increase in the FTA rate for both services.